Observations of the Antarctic Circumpolar Current Over the Udintsev Fracture Zone, the Narrowest Choke Point in the Southern Ocean. Issue 7 (4th July 2019) - Park, Y.‐H.; Park, T.; Kim, T.‐W.; Lee, S.‐H.; Hong, C.‐S.; Lee, J.‐H.; Rio, M.‐H.; Pujol, M.‐I.; Ballarotta, M.; Durand, I.; Provost, C.
Abstract: An up‐to‐date map of the Antarctic Circumpolar Current (ACC) fronts is constructed from the latest version of mean dynamic topography (MDT) from satellite altimetry and reveals the narrowest ACC width in the Udintsev Fracture Zone (UFZ), with the strongest concentration of the three major ACC fronts within a limited distance as short as 170 km, about 40% narrower than that at Drake Passage. At 144°W, at the entrance of the UFZ, which lies between the Pacific‐Antarctic Ridge (PAR) and its eastwardly offset segment (offset PAR segment), there is a triple confluence of the Subantarctic Front, Polar Front, and Southern ACC Front . Downstream of this longitude, the Subantarctic Front progressively meanders northward over the relatively shallow offset PAR segment before channeling through the Eltanin Fracture Zone, thus diverging from the Polar Front which proceeds through the UFZ. In situ observations from two recent cruises at 144°W confirm the satellite altimetry‐derived frontal circulation in the UFZ region and yield a baroclinic transport relative to the bottom of 113 × 10 6 m 3 /s, comparable to that through Drake Passage. The hydrographic sections show no Antarctic bottom water colder than 0.2 °C. Characteristics of major water masses are described, and the implications for their potential downstream modifications at Drake Passage are discussed in terms of the meridional overturning circulation across the ACC. Mesoscale eddy activity with periods shorter than 90 days is predominantly concentrated in the immediate downstream area of the offset PAR segment, suggesting a substantial poleward eddy heat flux there. Key Points: The Antarctic Circumpolar Current is only 170 km wide in the Udintsev Fracture Zone, forming the narrowest circumpolar choke point First observations of high‐quality hydrography in the Udintsev Fracture Zone show no Antarctic bottom water colder than 0.2 °C The Udintsev Fracture Zone is a suitable site for a long‐term monitoring of the Antarctic Circumpolar Current